Penerapan Strategi Pemasaran Marketing melalui Media Sosial Tadika Bijak Lestari Georgetwon Penang - Sonia Dalimunthe; Syahrul Amsari (Universitas Muhammadiyah Surabaya, 2023)
This study talks about how the execution of showcasing procedures completed by Tadika Bijak Lestari Georgetwon Penang utilizes online entertainment. The advantages of online entertainment as a showcasing device in the realm of schooling in the period of the Modern Upheaval 4.0 are extremely important decisions since they are progressively open to many individuals. Tadika Bijak Lestari Georgtwon Penang Malaysia is one of the tadika Lembaga branch situated at 20 medan Abstract− This study examines how the execution of showcasing procedures did by Tadika Bijak Lestari Georgetwon Penang utilizes web-based entertainment. The advantages of web-based entertainment as a showcasing device in the realm of schooling in the time of the Modern Upset 4.0 are extremely significant decisions since they are progressively open to many individuals. Tadika Bijak Lestari Georgtwon Penang Malaysia is one of the tadika Lembaga branch situated at 20 medan sungkai 20, Medan Sungkai, Taman Kampar, 10460 George Town, Penang, Malaysia Postal district 10460 penang island, possessed by Puan Siti Ruzita Binti Ramli. The witnesses in this study were chosen utilizing Purposive Testing methods to acquire the right data. This examination utilizes information assortment procedures through documentation, meetings, meetings, and writing, so the outcomes acquired are more exact. The outcomes showed that Tadika Bijak Lestari involves online entertainment as a showcasing device through the Facebook application, in practice Tadika Bijak Lestari, posts every activity carried out there to its Facebook account as an effort to introduce the public.